Faktor-Faktor Yang Berhubungan dengan Kejadian Stunting pada Balita di Puskesmas Rumbia Kabupaten Jeneponto - Yenni Yenni; Andi Tenri Angka (JURNAL KEPERAWATAN SISTHANA, 2018)
Stunting is defined as the condition of children aged 0 – 59 months, where the height for age is below minus 2 Standard Deviations (<-2SD) from the WHO median standard. The aim of the research is to determine the factors associated with the incidence of stunting in toddlers at Community Health Centers. Rumbia, Jeneponto Regency. The type of research used was an analytical survey with a cross sectional study approach. The sample was 72 toddlers in Rumbia village using a purposive sampling technique. The results of the research show that there is a relationship between maternal employment and the incidence of stunting in toddlers at the Rumbia health center, Jeneponto Regency with a p value = 0.034 < ? 0.05, there is a relationship between maternal education and the incidence of stunting among toddlers at the Rumbia health center, Jeneponto Regency with a p value = 0.003 < ? 0.05, there is a relationship between the number of children and the incidence of stunting in toddlers at the Rumbia health center, Jeneponto Regency with a p value = 0.016 < ? 0.05. Conclusion: There is a relationship between mother's employment, mother's education and number of children with the incidence of stunting among toddlers at the Rumbia Community Health Center, Jeneponto Regency.